Proposed Modeling of Natural Convection Cooling Heat Pipe (Journal of Nuclear Technology in Applied Science, 2022)
Heat-pipes and thermosyphons are considers as passive heat transfer appliances which, when properly designed and manufactured, have very long live spans when operating with temperature limits. Nuclear spent fuel storage tanks have continuous heat emission even after reactor shutdown. To keep spent fuel temperature within safe limit heat must be dissipated in regime of emergency nuclear reactor shut-down. This paper intends theoretical a completely passive cooling system using a wickless gravity assisted two-phase closed heat-pipe loop for dissipation the heat and cooling the nuclear reactor spent fuel pool by running as alternative cooling system to be in safe mode. The model considers natural convection by air for the condenser part of the heat-pipe loop to confine the residual heat. A numerical simulation using a new design of gravity assisted two-phase closed heat-pipe loops was used to investigate the heat-pipe performance and thermal characteristics. Heat-pipe configuration and heat load are well known. Focus on atmospheric air temperature effect will be analyzed. The heat-pipe material is stainless steel-AISI316 and demineralized water was used as the running working fluid. The atmospheric air at ambient temperature was naturally circulated around the heat-pipe condenser for cooling fluid. The results showed that the best thermal performance and characteristics were obtained at a lower atmospheric air temperature and the heat pipe could remove 150kW with safe conditions. The computer simulation refers to a pattern, and a trend line can then be used to predict the concepts of heat transfer with different inputs.
Keywords: Heat pipe; Natural convection; Theoretical modeling; Heat-pipe transient operation; Passive cooling system